2014
DOI: 10.1016/j.brat.2014.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Sudden gains in behavioural activation for depression

Abstract: Sudden gains have been linked to improved outcomes in cognitive behaviour therapy for depression. The relationship between sudden gains and outcome is less clear in other treatment modalities, including interpersonal psychotherapy and supportive expressive therapy, which may indicate different mechanisms of change between treatment modalities. The current study examined sudden gains in adults meeting diagnostic criteria for depression (N = 40) offered up to 12 sessions of behavioural activation treatment. Sudd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…These constructs refer to rapid changes either during the earlier phases of treatment (rapid early response; e.g., Fennell & Teasdale, 1987;Ilardi & Craighead, 1994) or during consecutive sessions throughout the treatment (sudden gains; e.g., Tang & DeRubeis, 1999). Research on change patterns during psychological treatments suggests that clinically relevant changes in symptom levels, even sudden gains, can occur very early in the treatment process, often between sessions one and five (Crits-Christoph et al, 2001;Doane et al, 2010;Dour, Chorpita, Lee, & Weisz, 2013;Fennell & Teasdale, 1987;Hunnicutt-Ferguson, Hoxha, & Gollan, 2012;Masterson et al, 2014). Rapid early responses and sudden gains have been attested across various treatment modalities and theoretical models (e.g., Kelly, Roberts, & Ciesla, 2005;Kelly, Cyranowski, & Frank, 2007;Stiles et al, 2003;Tang, Luborsky, & Andrusyna, 2002) and disorders (e.g., Aderka, Nickerson, Bøe, & Hofmann, 2012;Clerkin, Teachman, & Smith-Janik, 2008;Doane et al, 2010;Hofmann, Schulz, Meuret, Moscovitch, & Suvak, 2006;Present et al, 2008).…”
Section: Defining Brief Therapiesmentioning
confidence: 99%
“…These constructs refer to rapid changes either during the earlier phases of treatment (rapid early response; e.g., Fennell & Teasdale, 1987;Ilardi & Craighead, 1994) or during consecutive sessions throughout the treatment (sudden gains; e.g., Tang & DeRubeis, 1999). Research on change patterns during psychological treatments suggests that clinically relevant changes in symptom levels, even sudden gains, can occur very early in the treatment process, often between sessions one and five (Crits-Christoph et al, 2001;Doane et al, 2010;Dour, Chorpita, Lee, & Weisz, 2013;Fennell & Teasdale, 1987;Hunnicutt-Ferguson, Hoxha, & Gollan, 2012;Masterson et al, 2014). Rapid early responses and sudden gains have been attested across various treatment modalities and theoretical models (e.g., Kelly, Roberts, & Ciesla, 2005;Kelly, Cyranowski, & Frank, 2007;Stiles et al, 2003;Tang, Luborsky, & Andrusyna, 2002) and disorders (e.g., Aderka, Nickerson, Bøe, & Hofmann, 2012;Clerkin, Teachman, & Smith-Janik, 2008;Doane et al, 2010;Hofmann, Schulz, Meuret, Moscovitch, & Suvak, 2006;Present et al, 2008).…”
Section: Defining Brief Therapiesmentioning
confidence: 99%
“…Although the small sample and follow-up in this study was largely consistent with other studies of sudden gains (Aderka et al, 2012, Hunnicutt-Ferguson et al, 2012, Masterston et al, 2014, we were limited in our ability to test for moderation, indirect relationships and the long-term effects of sudden gains by the sample size. Larger trials with longer follow-up periods are needed.…”
Section: Limitations and Future Directionsmentioning
confidence: 69%
“…Interestingly, SGs can occur very early. Several studies have found that SGs are most likely to happen within the first three sessions (Dour, Chorpita, Lee, & Weisz, 2013;Hunnicutt-Ferguson et al, 2012;Masterson et al, 2014). Altogether, these results suggest 4 Early Sudden Gains in an ACT-based Intervention that a relatively large proportion of clients may benefit during the first few sessions and that these sudden improvements predict outcomes during and after interventions.…”
mentioning
confidence: 88%